The Effect of Heparinoid as Systemic Prophylactic Anticoagulants on COVID-19 Patient Mortality and Its Safety Profiles: A Systematic Review and Meta-Analysis - Anggarany, Ariska Deffy; Sauriasari, Rani; Alkaff, Muhammad; Takhwifa, Famila; Nufus, Hayatun; Paramita, Diana (Pharmaceutical Sciences and Research, 2021)
Coagulopathy is one of the complications of COVID-19 and is associated with a higher risk of mortality. However, evidence regarding the effectiveness and safety of anticoagulant therapy in various doses among COVID-19 patients is limited. This systematic review and meta-analysis aims to review and explore the effect of using heparinoids as a systemic anticoagulant at prophylactic doses on mortality in COVID-19 patients. Systematic searches were conducted of various databases (Pubmed, ScienceDirect, SpringerLink, Scopus, and ProQuest) covering the period 2019-2021. We assessed the quality of the articles using the STROBE checklist. Studies with a high risk of bias were excluded before pooled effect size was synthesized with 95% confidence intervals (CI) using random-effects models. From the 12 identified studies (N=8,968), six observational studies (N=7,176) were involved in the meta-analysis. The studies reviewed in the paper used a retrospective cohort design in various settings. The pooled effect size of mortality comparing prophylactic anticoagulant and no anticoagulant in three studies showed that there was an association between using prophylactic anticoagulant and a lower risk of in-hospital mortality (pooled OR= 0.47; 95% CI 0.19-0.76). A prophylactic dose of heparinoid anticoagulant was also associated with lower mortality (pooled OR= 0.51; 95% CI 0.21-0.82) and with lower bleeding events compared to intermediate-to-therapeutic dose anticoagulants. Administration of heparinoid anticoagulants at prophylactic doses was associated with reduced mortality risk in hospitalized COVID-19 patients. Due to the increased risk of bleeding with therapeutic doses, the use of prophylaxis anticoagulant is suggested in COVID-19 patients who are not critically ill.